On the genesis of secondary reservoirs of oil and gas at superdeep depths - Lukin, A. E.; Gaphich, I.P. (Reports of the National Academy of Sciences of Ukraine, 2016)
The presence of high-yield reservoirs of oil and gas in the Lower Carboniferous at a depth of more than 6 km is caused by the action of ascending plumetectonic high-enthalpy fluids upon intensively compressed (with practically total reduction of sedimentary porosity) sedimentary rocks. These processes are connected with neo- and actuotectonic stages of the evolution of deep sedimentary basins. The current helium-hydrogen "blowing-up" is of special importance in the formation of such reservoirs. It provides both a purely physical deconsolidation ("gas" porosity and fracturing) and physicochemical processes of leaching and acid dissolution.